Tuberculosis in HIV-Associated Cryptococcal Meningitis is Associated with an Increased Risk of Death - Rutakingirwa, Morris K. (J Clin Med, 2020)
Tuberculosis (TB) and cryptococcal meningitis are leading causes of morbidity and mortality in advanced HIV disease. Data are limited on TB co-infection among individuals with cryptococcal meningitis. We performed a retrospective analysis of HIV-infected participants with cryptococcal meningitis from 2010–2017. Baseline demographics were compared between three groups: ‘prevalent TB’ if TB treated >14 days prior to cryptococcal meningitis diagnosis, ‘concurrent TB’ if TB treated ± 14 days from diagnosis, or ‘No TB at baseline’. We used time-updated proportional-hazards regression models to assess TB diagnosis as a risk for death. Of 870 participants with cryptococcal meningitis, 50 (6%) had prevalent TB, 67 (8%) had concurrent TB, and 753 (86%) had no baseline TB. Among participants without baseline TB, 67 (9%) were diagnosed with incident TB (after >14 days), with a median time to TB incidence of 41 days (IQR, 22–69). The 18-week mortality was 50% (25/50) in prevalent TB, 46% (31/67) in concurrent TB, and 45% (341/753) in the no TB group (p = 0.81). However, TB co-infection was associated with an increased hazard of death (HR = 1.75; 95% CI, 1.33–2.32; p < 0.001) in a time-updated model. TB is commonly diagnosed in cryptococcal meningitis, and the increased mortality associated with co-infection is a public health concern.